1280 Improving exposure assessment methodologies for epidemiological studies on pesticides. (24th April 2018) - Galea, Karen; Basinas, Ioannis; Cherrie, John; Vermeulen, Roel; Kromhout, Hans; Jones, Kate; Harding, Anne-Helen; Tongeren, Martie van; Povey, Andrew
Abstract : Introduction: The presentation describes a comprehensive study to better understand the reliability of assessment of human exposure to plant protection products (PPP) in previous occupational epidemiological investigations, and to use this information to recommend improvements in scientific practice for future studies. Further, it aims to assess the reliability and external validity of surrogate measures used in these studies to assign exposure to individuals or groups of individuals on the basis of self-reported information, job/crop exposure matrices and exposure algorithms. The project will also evaluate the size and the effects of recall bias on the misclassification of exposure to PPPs and associated health effects. Methods: Existing and newly collected (biological) monitoring data from several existing epidemiological studies and historical records across various populations in Europe, Africa and Asia. Urinary metabolites of pesticides will be selected with due consideration on the extent of use within the study populations, validity of biomonitoring methods etc. The performance of the various exposure assessment methods will be compared and contrasted within existing epidemiological studies. Results: The main outcome will be the validation of widely accepted and easily adaptable semi-quantitative individual-based exposure assessment methods against measured levels of urinary PPP metabolites in a broad range of settings. Additionally, the study will compare the reliability and performance of several grouped- and individual-based exposure assessment methods in the frame of existing epidemiological studies. Conclusion: The project is due to commence in September 2017. We propose to present the study protocols, rationale and outcomes of a mini-symposium to be held at EPICOH 2017. © British Crown copyright (2017). This work is funded by the European Crop Protection Association (ECPA). The Health and Safety Laboratory is the commercial arm of the Health and Safety Executive (HSE); the paper's contents including any opinions and/or conclusions expressed, are those of the authors alone and do not necessarily reflect ECPA or HSE policy.